1p36 Deletion Syndrome and the Aorta: A Report of Three New Patients and a Literature Review - Valentina Lodato (MDPI AG, 2021)
Background: Monosomy 1p36 syndrome is now considered the most common terminal deletion syndrome, with an estimated incidence of 1 in 5000. Cardiac involvement is well described in the literature mainly in terms of congenital heart defects (CHDs) and cardiomyopathies (CMPs). Few data in the literature describe the potential progressive nature of aortic dilatation (root and ascending aorta) in 1p36 deletion syndrome. SKI harboured in the deleted region might play a predisposing factor for this aspect. Methods: we reviewed the aortic aspect both in the literature and in our cohort, where major attention to the aortic abnormalities was given through dedicated echocardiographic measurements even in previously screened individuals. Results: aortic involvement in 1p36 deletion syndrome was described in the literature three times within the CHD context. We observed three additional patients from our cohort (three out of nine patients) with aortic dilatation. All patients with dilated aorta had SKI haploinsufficiency within the deleted region. Conclusions: at long-term outcome and with a growing population of this rare disease, this association (1p36 deletion and aortic dilatation) might represent a major concern especially in terms of risk stratification and the potential need for specific management (conservative pharmacologic and eventually surgical) whenever indicated. The present study suggests the need for detailed multicentric studies and indication to periodic echocardiographic screening in addition to baseline tests, especially in individuals with deletions harbouring SKI.